Comparison of the Effectiveness Lateral Position 30 Degrees and 90 Degrees on Decubitus Events in Stroke Patients - Latipah, Siti; Sofiani, Yani; Yunitri, Ninik; Mulyatsih, MG Enny; Sulistyorini, Cahyo Ismawati (STIKep PPNI Jawa Barat, 2024)
Aims: Stroke is the second leading cause of death and disability globally, characterized by sudden neurological deficits. Pressure ulcers, caused by prolonged bed rest, can be managed non-pharmacologically through immobilization and routine tilting to prevent decubitus. To compare the effectiveness of the lateral position with an inclination of 30 and 90 degrees on the risk of decubitus in stroke patients, in this study the control group was tilted 90 degrees and the intervention group was tilted 30 degrees. Method: The sampling method is non-probability sampling with purposive sampling, a sample of 22 patients. Results: Data analysis using Reapeted Measurement Anova resulted in a value in the experimental group resulting in a sum of square value of 24.9, f value 14.3, P < 0.001, while in the control group a sum of square value of 76.5, f value 26.8, P < 0.001 was obtained, so it can be concluded that the lateral position with an inclination of 90 degrees and 30 degrees has the same effect, namely providing a significant influence on reducing the risk of decubitus. Conclusions: The study reveals that stroke patients aged 56-65 have a higher risk of pressure ulcers, with low-weight patients at higher risk. Early lateral position intervention and nutrition can significantly reduce the risk of decubitus, highlighting the importance of early wound healing.